Towards Deep Arabic Language Learning: Designing Materials that are Mindful, Meaningful, and Joyful - Muh. Sabilar Rosyad; Saleh Muhammad Kabir (Jurnal Pendidikan Bahasa Arab, 2025)
This research investigates integration of mindfulness, meaningfulness and joyfulness in Arabic language materials in Islamic higher education. Through a qualitative multiple-case study in three schools, data were collected through instructor interviews, document analyses of syllabi and learning resources, as well as classroom observations. Results suggest that mind-opening practices will increase students’ attentional preparation and reflective engagement, that soul-stirring materials will support personal and spiritual relevance and, that joy-filled experiences will create emotional connection and sustained motivation. These principles are in tune with deep learning aims through engaging higher-order cognition, metacognitive awareness, and a depth of experience. Nevertheless, there are several obstacles such as lack of training for advanced material design, aversion to new techniques and technological limitations. The research finds that the use of a mindful-meaningful-joyful framework enhances Arabic pedagogy, and creates a connection between language learning and cognitive, affective, and spiritual areas. It demands infrastructure investments, teacher training and curriculum redevelopment to support rigorous but deeply humanizing Arabic instruction.